2021
DOI: 10.1126/sciadv.abg1601
|View full text |Cite
|
Sign up to set email alerts
|

Microglial dyshomeostasis drives perineuronal net and synaptic loss in a CSF1R +/− mouse model of ALSP, which can be rescued via CSF1R inhibitors

Abstract: Adult-onset leukoencephalopathy with axonal spheroids and pigmented glia is an autosomal dominant neurodegenerative disease caused by mutations in colony-stimulating factor 1 receptor (CSF1R). We sought to identify the role of microglial CSF1R haploinsufficiency in mediating pathogenesis. Using an inducible Cx3cr1CreERT2/+-Csf1r+/fl system, we found that postdevelopmental, microglia-specific Csf1r haploinsufficiency resulted in reduced expression of homeostatic microglial markers. This was associated with loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 91 publications
4
57
0
Order By: Relevance
“…A study, in which adult CSF1R± mice were treated with persistent low-grade PLX5622 at different stages of the disease, has found that modulating microglial phenotypes could reverse presynaptic and ECM alterations induced by CSF1R haploinsufficiency and improved cognition without altering neuronal populations. This finding suggests that microglia are viable targets for therapeutic intervention early in the disease ( Arreola et al, 2021 ).…”
Section: Based On the Proliferation Of Resident Microgliamentioning
confidence: 99%
“…A study, in which adult CSF1R± mice were treated with persistent low-grade PLX5622 at different stages of the disease, has found that modulating microglial phenotypes could reverse presynaptic and ECM alterations induced by CSF1R haploinsufficiency and improved cognition without altering neuronal populations. This finding suggests that microglia are viable targets for therapeutic intervention early in the disease ( Arreola et al, 2021 ).…”
Section: Based On the Proliferation Of Resident Microgliamentioning
confidence: 99%
“…Homozygous CSF1R mutations in the human brain lead to almost complete absence of microglia ( Oosterhof et al, 2019 ). Using an inducible Cx3cr1 CreERT2/+ ; Csf1r fl/+ system to conditional delete one Csf1r allele also affects microglial homeostasis ( Arreola et al, 2021 ). CSF1R is highly conserved among vertebrates, including zebrafish, which possess two paralogous genes: csf1ra and csf1rb .…”
Section: Physiological Role Of Csf1r In the Central Nervous Systemmentioning
confidence: 99%
“…Hence, potential effects of CSF1R or CSF1R-mediated microglia depletion on DNs formation may also play important role in neuropathology of ALSP and AD. CSF1R inhibitor PLX5622 prevented the loss of presynaptic surrogates and the extracellular matrix (ECM) structure perineuronal nets in Csf1r +/– mice ( Arreola et al, 2021 ). An induced pluripotent stem cell line from a patient with ALSP has been generated, which may allow the investigation of CSF1R mutations in a human cell model and shed new light on the therapeutic strategies of this intractable ALSP ( Hayer et al, 2018b ).…”
Section: Csf1r In Neurodegenerative Diseasesmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted March 12, 2022. ; https://doi.org/10.1101/2022.03.09.483490 doi: bioRxiv preprint synaptic and neuronal loss (Arreola et al, 2021;Elmore et al, 2018;Hong et al, 2016;Rice et al, 2015;Schafer et al, 2012;Spangenberg et al, 2016;Wang et al, 2020;Werneburg et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…During AD, microglia mount an inflammatory response to Aβ plaques, as evidenced by findings in both human AD brains and animal models of the disease (Leng and Edison, 2021; Sayed et al, 2021). Accumulating evidence implicates microglia in several AD- related processes including plaque formation and growth (Spangenberg et al, 2019), plaque compaction (Casali et al, 2020; Spangenberg et al, 2019), constituting a protective barrier against dystrophic neurites (Condello et al, 2015), promoting or preventing development and spreading of Tau pathology (Shi et al, 2019), cerebral amyloid angiopathy (Spangenberg et al, 2019), destruction of perineuronal nets (Arreola et al, 2021; Crapser et al, 2020), as well as synaptic and neuronal loss (Arreola et al, 2021; Elmore et al, 2018; Hong et al, 2016; Rice et al, 2015; Schafer et al, 2012; Spangenberg et al, 2016; Wang et al, 2020; Werneburg et al, 2020).…”
Section: Introductionmentioning
confidence: 99%